A rare case of oral lymphangioma of tongue - Erugula, Sridhar Reddy; MVS, Sudheer; Sameera, Ayesha; Vujhini, Sudhir Kumar; Kandukuri, Mahesh Kumar (International Journal of Contemporary Pediatrics, 2016)
Lymphangiomas are congenital benign tumors of lymphatic vessels, which are localized in the head and neck area in about 75% of cases. Most cases occur in the head and neck region. Oral cavity lymphangiomas are rare. We here describe one such rare case of lymphangioma involving the tongue and was successfully treated with laser therapy.